Mother’s Satisfaction towards Childbirth Care at Public Health Centers in Bench-Maji Zone, Ethiopia: A Facility-Based Cross-Sectional Study - Hailemariam, Shewangizaw; Genetu, Amare; Sahile, Ermiyas (International Journal of Reproductive Medicine, 2020)
Background. Assessing the level of maternal satisfaction towards maternal health care services has a paramount importance in improving the service quality and enhancing service utilization. Hence, the aim of this study was to assess maternal satisfaction towards childbirth care and its determinants at public health facilities in Bench-Maji Zone, Ethiopia. Methods. A facility-based cross-sectional study was conducted from May 20, 2018, to July 11, 2018 in Bench-Maji Zone, Ethiopia. A total of 845 mothers were selected by employing a systematic random sampling technique. Data were collected using a pretested and structured questionnaire. Satisfaction was measured by the five-point Likert scale from very dissatisfied (1) to very satisfied (5). Data were entered in to Epi data version 3.1 and analyzed using SPSS version 20. A P value < 0.05 was considered to declare statistical significance. Result. About 506 (63.25%) of the mothers were satisfied by the overall care provided during childbirth. Factors associated with mothers’ satisfaction with childbirth care includes attending no formal education [AOR=3.69; 95% CI (1.99, 7.91)], rural residency [AOR=2.63; 95% CI (1.43, 5.80)], perceived measure taken to assure privacy [AOR=3.56; 95% CI (1.25, 7.41)], and attending antenatal care [AOR=6.23; 95% CI (3.42, 12.87)]. Conclusion. The overall satisfaction of mothers with childbirth care in public health centers of Bench-Maji Zone is low when compared with other studies. Hence, understanding mothers’ expectations, assuring privacy, and enhancing antenatal care attendance might improve maternal satisfaction with childbirth care.